Successes and final challenges along the HIV care continuum with transwomen in San Francisco. Issue 4 (29th April 2019) - Baguso, Glenda N; Turner, Caitlin M; Santos, Glenn‐Milo; Raymond, H Fisher; Dawson‐Rose, Carol; Lin, Jess; Wilson, Erin C
Abstract: Introduction: To examine the HIV care continuum for transwomen living in San Francisco and to determine factors associated with poor HIV‐related health outcomes. Methods: Data were collected from 2016 to 2017 with transwomen in San Francisco. Respondent‐driven sampling (RDS) was used to recruit a population‐based sample. Bivariate associations were assessed, and RDS‐weighted multivariable logistic regression was used to identify associations between exposures and outcomes along the HIV care continuum. Results: Of the 123 self‐identified transwomen in this analysis, ages ranged from 23 to 71 years with a majority identifying as Latina (40.8%) and African American (29.2%). An estimate of 14.3% of participants were not engaged in care, 13% were not currently on antiretroviral therapy (ART), 22.2% had a self‐reported detectable viral load and 13.5% had unknown viral load. Those using hormones had lower odds of not being on ART compared to those who did not use hormones. Those with unstable housing had a higher relative risk ratio of having a detectable viral load. Those who experienced both anti‐trans discrimination and racism had higher odds of not being in HIV care. Conclusions: San Francisco has made substantial progress engaging transwomen in the HIV care continuum, but the final push to ensure viral suppression will require addressing social determinants. Future interventions to increase HIV care engagement, ART use and viral suppression among transwomen must address housing needs and risks related to the overlapping effect of both anti‐trans discrimination and racism.